2006
DOI: 10.1128/jcm.44.4.1335-1341.2006
|View full text |Cite
|
Sign up to set email alerts
|

Is Serological Testing a Reliable Tool in Laboratory Diagnosis of Syphilis? Meta-Analysis of Eight External Quality Control Surveys Performed by the German Infection Serology Proficiency Testing Program

Abstract: Moreover, 10.2% of laboratories wrongly reported serological evidence for active infection in samples from patients with past syphilis or in sera from seronegative blood donors. Consequently, the continuous participation of laboratories in proficiency testing and further standardization of tests is strongly recommended to achieve better quality of syphilis serology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 11 publications
0
31
1
5
Order By: Relevance
“…In fact, the interpretation of the agglutination assay result strongly depends on the quality of the testing and the experience of the laboratory personnel. For this reason, it is often difficult to compare results from different laboratories (8).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the interpretation of the agglutination assay result strongly depends on the quality of the testing and the experience of the laboratory personnel. For this reason, it is often difficult to compare results from different laboratories (8).…”
Section: Discussionmentioning
confidence: 99%
“…Studies from STD clinics and Antenatal groups have shown seroprevalence ranging from 5.4% to 8.2% and 0.84% to 0.98% respectively (Maity et al, 2011;Archana et al, 2014). Antibody detection by non treponemal/ cardiolipin and treponemal tests are the mainstay for diagnosing syphilis and for monitoring the success of subsequent antibiotic treatment (Centers for Disease Control and Prevention, 2010;Müller et al, 2014). So the main aim of the present study was to understand the occurrence of syphilis among various patient groups attending a tertiary care hospital.…”
Section: International Journal Of Current Microbiology and Applied Scmentioning
confidence: 99%
“…The use of multiple antitreponema detection assays may be prudent for prenatal screening. 22 False-negative HIV and HTLV-1 testing have not been reported post-HSCT. 23 Infective serology screens are mandatory in both donor and recipient before HSCT, and the records should be consulted.…”
Section: Serological Testsmentioning
confidence: 99%